Monolithic ionizing particle detector based on active matrix of functionally integrated structures - Murashev, V.N.; Legotin, S.A.; Karmanov, D.E.; Baryshnikov, F.M.; Didenko, S.I. (Journal of alloys and compounds, 2014)
•A new type of monolithic silicon position detector is presented.•An operating principle, design and technology of the detector are described.•Calculated estimations of the detecting efficiency are carried out.•Experimental results of alpha-particle and electron detection are shown. An operating principle, design and technology of a new type of the monolithic silicon position detector (MSPD) for registration of ionizing particles and photons are described. The detector represents a specialized monolithic silicon VLSI that contains a two-dimensional detecting matrix of active functionally integrated bipolar structures and peripheral electronic circuitry for signal amplification and processing. This paper presents experimental results of α-particles and electrons detection with position accuracy and operation speed better than 12.5μm and 1ns, respectively. The givenestimations show the capabilities of this detector and its advantages in comparison with analogs.